POTENSI OLAHRAGA DAYUNG DI SUNGAI BATANGHARI JAMBI - ROLI MARDIAN (Cerdas Sifa Pendidikan, 2015)
ABSTRAK The river of Batanghari as known as the longest river in Sumatra Island, it is looks like “cutting” Sumatra island and almost make Sumatra island become two part in case we take a look it from upper course to lower course. The river of Batanghari size is + 3322 km and it makes Batanghari four times larger than Musi river. With the existence of this river hopefully and possibly could create the potential of water sport form here. From the most of paddle athletes that raised and took a part in national and international events are located and come from around Batanghari river. The paddle athlete should need a high body, long range of hand and good aerobic endurance based on the theory, so test and measurement were created toward students who located in around of Batanghari river and hopefully the talented athletes could be found and become the next generation of current paddle athletes. Keywords: The river of batanghari, potential of canoing sport, talent  athletes.